California Quail in Western Oregon: A Review - John A. Crawford (National Quail Symposium Proceedings, 2017)
Habitat use by California quail (Callipepla californica) was studied at the E. E. Wilson Wildlife Area in northwestern Oregon, a mesic extension of the range of this species, from 1974 to 1992. Abundance of quail on the area was related to plant succession. Dietary studies revealed that legumes-particularly deervetch (Lotus spp.), peavine (Lathyrusspp.), Scot's broom (Cytisusscoparius), and vetch (Viciaspp.)-oomposed 67% of the relative dry mass of the annual diet. California quail typically nested in shrub/grassland and roadside habitats with less grass and shrub cover and more bare ground than at random locations within those cover types. Blackberry (Rubus spp.) stands were used consistently for roosts and were the most frequently used escape cover. Abundance and productivity measures of California quail on treated sites-including disked areas, food plots, and wheat plantings revealed most birds (on a year-round basis) were found on disked areas and most chicks were produced on these sites. Fewest young hatched on food plots and wheat plantings and the latter had the lowest abundance of breeding adults. Most important food and cover plants responded positively to prescribed burning and disking but returned to pretreatment levels of abundance within 2-3 years. I concluded that the successful introduction of California quail into the Willamette Valley and abundance and productivity of these populations were related to the presence of certain early seral species of plants, particularly some exotic species, and plant succession
Keywords: California quail; Callipepla californica; habitat management; Oregon